CODE SWITCHING AND CODE MIXING IN #NEBENG BOY - Linda Yuana (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2022)
As a social creature, human beings need society to live in. There is always a power to survive in society including being survive to communicate. In exchanging the message to one another, people use language and some strategies in purpose of being successful to deliver meaning that they want. Among those strategies, there are code switching and code mixing, which is used when people communicate in multilingual society. Code switching is when a speaker uses strategy to switch from one language to another, whether code mixing is when a speaker mix the language and use it in an utterance. In this study, the object of the research is a Youtube channel called #nebengboy. This channel hosted by bilingual talented Indonesian host who usually speak fluent both in Indonesian and English. The finding shows that there are many types of code switching and code mixing use in the conversation of this Youtube channel, both by the host and the guest. From the findings, it can be concluded that the host, uses many code switching and code mixing for some reasons. This reasons can be one of the consideration for people to create a successful and meaningful communication in multilingual society.